AN INCREASE IN IPS LEARNING ACHIEVEMENT THROUGH THE DEMONSTRATION METHOD IN KELAS II SDN 2 NGANDONG GANTIWARNO KLATEN - Sri Suwartini; Sudiyo Widodo (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The problem studied in this study is how to improve learning achievement on with the Demonstarsi method in class II students of SDN 2 Ngandong ,Gantiwarno, Klaten The discussion of the description of this research is how the teacher increases the students' ability to carry out demonstrations. The research method used was action research by determining the steps: planning, implementing, collecting data, and reflecting on each step using two cycles. The results of the study from the first cycle only 81.57% or 16 students who scored above the KKM while 18.43% or 5 students got grades below the KKM. Because it has not yet reached the KKM, the researchers proceed to cycle II. In cycle 2 there was a significant increase in which 89.47% of students had mastered the competencies that had been set. Out of the 21 students, 19 students have met the specified KKM. From the results of the implementation of the first cycle and second cycle, it can be concluded that using the demonstration method can improve the learning achievement of the theme "My family" grade II students at SDN 2 Ngandong, Gantiwarno, Klaten.